Analysis of Factors Affecting the Length of Job Search for Educated Workers in Nusa Tenggara Barat (NTB) Province - Erina Wulandari; Luluk Fadliyanti; Vici Handalusia Husni (Tinta Emas Institute, 2023)
This study aims to analyze the effect of education level, age, gender, wage, and job training on the duration of job search in West Nusa Tenggara Province. This study uses a type of research that is quantitative with secondary data. Data is obtained from SAKERNAS in 2023. The amount of data obtained was 190 educated workers. The analytical tool used is multiple linear regression, determination coefficient test (R2), t test and simultaneous regression coefficient significance test (f test). The results of this study indicate that the variables of education level, age, gender, wage, and job training simultaneously have a significant effect on the length of time looking for work. While the value of R2 is 0.062, this means that 6.2% of the length of time looking for work of educated workers is influenced by the variables above and the rest is influenced by other variables outside this study.